Subjective sleep dysfunction and insomnia symptoms in Parkinson's disease: Insights from a cross-sectional evaluation of the French CoPark cohort - Ratti, Pietro Luca (2015)
Introduction: Twenty-seven to 80% of patients with Parkinson's Disease (PD) complain of subjective sleep dysfunction and insomnia symptoms. Our aim is to describe the prevalence and features of subjective sleep dysfunction and insomnia symptoms in patients with PD compared to other patients. Methods: Cross-sectional analysis of 636 adult PD patients compared to 143 age and sex-matched non-PD control patients consulting their general practitioners. Insomnia symptoms and other sleep features were assessed by the Pittsburgh Sleep Quality Index (PSQI), a global score > 5 defining impaired sleep. The Chi-square test or the Student's t-test were used to assess the potential clinical and demographic differences between groups and between PD patients with vs. without sleep dysfunction. Logistic regression analysis was employed to test multivariate effects. Results: Sleep dysfunction and insomnia symptoms were more frequent in PD patients compared to control patients (63 vs. 45%, p = 0.001). Female gender, PD duration, presence of depression and anxiety were associated with the presence of insomnia in PD. Subjective sleep efficiency, habitual sleep quality, sleep disturbance and daytime dysfunction, but not sleep latency, were reduced in PD patients compared to controls. Conclusions: The prevalence of sleep dysfunction is higher in PD than in other general medical conditions. Insomnia in PD seems to affect sleep maintenance and consolidation, but not sleep onset.